Vascular endotelial dysfunction is a pathogenetic factor in the development of neurodegenerative diseases and cognitive impairment - N. V. Goncharov; P. I. Popova; A. S. Golovkin; N. M. Zalutskaya; E. I. Palchikova; K. V. Zanin; Р. V. Avdonin (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2020)
The amount of publications devoted to the endothelial cells, on the one hand, and neurological diseases, on the other hand, has been growing rapidly in recent years. Nevertheless, the relationship between the endothelial monolayer and the cells of the nervous system remains poorly studied. This review presents the available information about endothelial markers, molecular and cellular mechanisms for maintaining the integrity of the endothelial monolayer and the violations in some acute and chronic neuropsychiatric diseases. At the molecular level, the most important pathogenetic link in endothelial dysfunction is an imbalance of Ca2+ ions, which is associated with redox imbalance in the cells and increased generation of reactive oxygen species. Genetic and epigenetic factors that cause these disorders and their cause-and-effect relationships are considered. Of the genetic diseases, the most studied are monogenic diseases associated with impaired blood-brain barrier integrity: this is a deficiency of protein molecules that ensure glucose transport, structural and functional integrity of tight junctions and the basement membrane of endothelial cells themselves, as well as mutations in pericytes and smooth muscle cells. Mutations that increase the risk of developing known neurodegenerative diseases, but are also the cause of cerebrovascular pathology, are less studied. The small vessel diseases constitute a whole group of primarily epigenetically caused diseases, the clinical consequence of which is often vascular dementia. Special attention is paid to one of the least studied problems—the pathogenesis of toxicological diseases that occur at different times after acute and chronic organophosphate poisoning. Microangiopathies caused by damage to the endothelium in the central and peripheral nervous systems can be the main cause for the development of delayed effects in organophosphate poisoning. In the absence of effective therapies for neurodegenerative diseases, more and more evidence is emerging about the positive impact of the nutritional structure and healthy lifestyle on the state of blood vessels and the risk of developing these diseases.